Relevansi Pemikiran Tasawuf Syekh Nawawi Al-Bantani Dengan Ekonomi Islam - asyari hasan (Syifa al-Qulub, 2022)
In today's postmodern era, there are many problems related to economic activity, both in the form of ethics and practice. The purpose of this study is to analyze the Sufism thought of sheik nawawi al-bantani and to see its relevance to Islamic economics in the contemporary era. The method used by the author is descriptive qualitative method, using library research based on the book Salalim al-Fudhala '' ala Hidayat al-Adzkiya 'ila Thariq al-Auliya' by Syekh Nawawi Al-Bantani and at the same time being the primary data in this study. . Meanwhile, secondary data in this study are in the form of the holy book al-Qur'an, hadiths, books and journals on Sufism and Islamic economics. The results of the study show that there are those who display several principles between Sufism and Islamic economics, such as being both concerned with needs and oriented towards God. The relevance can be seen in various aspects of economic activity, such as consumption, employment and income.